Acceptance of Flu Vaccine among Parents of Diabetic Children in Jordan - Walid Al-Qerem; Anan Jarab; Judith Eberhardt; Fawaz Alasmari; Alaa Hammad; Sarah Abu Hour (Vaccines, 2024)
There is a critical need to understand vaccine decision-making in high-risk groups. This study explored flu vaccine acceptance among Jordanian parents of diabetic children. Employing a cross-sectional approach, 405 parents from multiple healthcare centers across Jordan were recruited through stratified sampling, ensuring a broad representation of socioeconomic backgrounds. A structured questionnaire, distributed both in-person and online, evaluated their knowledge, attitudes, and acceptance of the flu vaccine for their diabetic children. The results indicated that only 6.4% of the study sample reported vaccinating their children against the flu annually, and only 23% are planning to vaccinate their children this year. A multinomial logistic regression analysis revealed notable variability in responses. Specifically, parents with a positive attitude towards the flu vaccine and those with older children had less odds to reject the vaccine (OR = 0.589, 95% CI (0.518–0.670), p < 0.001 and OR = 0.846, 95% CI (0.736–0.974), p = 0.02, respectively). Conversely, prevalent misconceptions regarding vaccine safety and efficacy emerged as significant barriers to acceptance. Our findings advocate for targeted educational programs that directly address and debunk these specific misconceptions. Additionally, strengthened healthcare communication to provide clear, consistent information about the flu vaccine’s safety and benefits is vital to help enhance vaccine uptake among this vulnerable population, emphasizing the need to address specific concerns and misinformation directly.